Why Is Executive Compensation So High? A Model of Executive Compensation - HARASHIMA, Taiji (Journal of Advanced Research in Management, 2019)
In this paper, I examine the mechanism of extremely high executive compensation based on the concept of ranking value and preference, and show that the origin of such extremely high compensation is economic rents. Ranking value and preference provide monopoly powers, profits, and rents to producers and generate “superstars” who are not only absolutely but, more importantly, are relatively superior to other executives. Furthermore, ranking value and preference enable a firm’s product to be differentiated and provide the firm monopoly rents (profits). Executives who contribute to differentiating the product can obtain economic rents and be compensated similar to superstars on professional sports teams. The monopoly rents owing to ranking values can be socially justified, but they may not be socially justifiable if they are solely distributed to executives.